Comprehensive analysis of potential immunotherapy genomic biomarkers in 1000 Chinese patients with cancer. (4th July 2019) - Zang, Yuan‐sheng; Dai, Chun; Xu, Xiaoman; Cai, Xin; Wang, Guan; Wei, Jinwang; Wu, Angela; Sun, Wending; Jiao, Shunchang; Xu, Qiang
Abstract: Background: Tumor mutation burden (TMB), DNA mismatch repair deficiency (dMMR), microsatellite instability (MSI), and PD‐L1 amplification (PD‐L1 AMP) may predict the efficacy of the PD‐1/PD‐L1 blockade. With the broadening landscape of immunotherapy use, it is important to identify patients who are likely to benefit from the therapy. This study aimed to characterize the distributions of these biomarkers and explore the relationships among these biomarkers for Chinese patients with cancer. Methods: In this study, we examined the aforementioned biomarkers in more than 1000 Chinese patients with cancer. These biomarkers were determined based on whole‐exome sequencing (WES) of tumor/blood samples. Results: Of the 953 samples from Chinese cancer patients assessed in this study, 35% exhibited high TMB (TMB‐H), 4% were positive for high MSI (MSI‐H), dMMR occurred in 0.53%, and PD‐L1 AMP was positive in 3.79%. We found higher rates of TMB‐H among hepatocellular carcinoma, breast cancer, and esophageal cancer patients than was reported for The Cancer Genome Atlas (TCGA) data. Lung cancer patients with EGFR mutations had significantly lower TMB values than those with wild‐type EGFR, and increased TMB was significantly associated with dMMR in colorectal cancer (CRC). The frequency of tumors with MSI‐H was the highest in CRC and gastric cancer. PD‐L1 AMP occurred most frequently in lung squamous cell carcinoma and HER2‐positive breast cancer. While MSI and dMMR are associated with higher mutational loads, correlations between TMB‐H and other biomarkers, between MSI‐H and dMMR, and between PD‐L1 AMP and other biomarkers were low, indicating different underlying causes of the four biomarkers. Conclusion: The results reveal the frequency of these biomarkers in different malignancies, with potential implications for PD‐1/PD‐L1 blockade use for Chinese patients with cancer. Abstract : Our study showed that incidence rates among 953 Chinese cancer patients of TMB‐H, MSI‐H, dMMR, and PD‐L1 AMP were 35%, 4%, 0.53%, and 3.79%, respectively. These findings may provide important information prior to administration of PD‐1/PD‐L1 blockade treatment to Chinese patients with cancer.